New Antifungal Compound: Impact of Cosolvency, Micellization and Complexation on Solubility and Permeability Processes - Tatyana V. Volkova (MDPI AG, 2021)
Poor solubility of new antifungal of 1,2,4-triazole class (S-119)—a structural analogue of fluconazole in aqueous media was estimated. The solubility improvement using different excipients: biopolymers (PEGs, PVP), surfactants (Brij S20, pluronic F-127) and cyclodextrins (α-CD, β-CD, 2-HP-β-CD, 6-O-Maltosyl-β-CD) was assessed in buffer solutions pH 2.0 and pH 7.4. Additionally, 2-HP-β-CD and 6-O-Maltosyl-β-CD were proposed as promising solubilizers for S-119. According to the solubilization capacity and micelle/water partition coefficients in buffer pH 7.4 pluronic F-127 was shown to improve S-119 solubility better than Brij S20. Among biopolymers, the greatest increase in solubility was shown in PVP solutions (pH 7.4) at concentrations above 4 w/v%. Complex analysis of the driving forces of solubilization, micellization and complexation processes matched the solubility results and suggested pluronic F-127 and 6-O-Maltosyl-β-CD as the most effective solubilizing agents for S-119. The comparison of S-119 diffusion through the cellulose membrane and lipophilic PermeaPad barrier revealed a considerable effect of the lipid layer on the decrease in the permeability coefficient. According to the PermeaPad, S-119 was classified as a highly permeated substance. The addition of 1.5 w/v% CDs in donor solution moves it to low-medium permeability class.